Globalization, Scientific Lexicons, and the Future of Biology. Issue 3 (1st September 2017) - Keller, Evelyn Fox
Abstract : For well over a century, temporality has played little more than a fleeting role in most of our biological sciences, and perhaps especially in genetics. For too long we have tried to build our understanding of genetic processes out of nouns, around entities. Perhaps it is time for a science constructed in and around the dynamics of biological processes, a genetics built not from nouns but from verbs. Perhaps the term gene itself can be revived for the twenty-first century by refiguring it as a verb. Would this be possible? Certainly our commitment to a noun-based science, to entity realism, runs deep, perhaps as deep as our understanding of science itself. Yet this article puts forward the suggestion that alternative linguistic traditions—rooted more in verbs than in nouns—might help us to develop a lexicon more suited to the dynamic interactivity of living systems to which current research in systems biology introduces us.